TRANZICIJA U PRIPOVJEDNIM I DRAMSKIM TEKSTOVIMA VINKA MÖDERNDORFERA (Филолошки студии, 2019)
After the collapse of the former Republic of Yugoslavia, the newlyformed independent countries were, almost simultaneously, forced to attend an intensive course in democracy and capitalism. The rather large, but hitherto suppressed and somehow denied cultural and civilisational differences between the former republics surfaced at the same time. We could say that Slovenia has always been considered a part of the Central European cultural circle rather than a part of the Balkans, thus finding itself on the rather bipolar socio-cultural crossroads. The general impression is that the Slovenians deal with their communist past more successfully than their neighbouring nations; perhaps the fore-mentioned civilisational gap could be the reason for that. The essay “Transition in narrative and dramatic texts of Vinko Möderndorfer” is actually an abbreviated version of the elaborate study on the manner in which political transition has been presented in contemporary Slovenian literature by analysing the narrative and dramatic works of Vinko Möderndorfer (b. 1958), a contemporary writer and director. The texts were chosen mainly on the basis of frequency of transitional elements. Also, the study deals with the overall coexistence of postmodernism, transitional literature and globalisation, but it also addresses the question of the reader’s perception.